Flavonoid Intakes in the US Diet Are Linked to Higher Socioeconomic Status and to Tea Consumption: Analyses of NHANES 2011–16 Data. Issue 8 (29th May 2020) - Vieux, Florent; Maillot, Matthieu; Rehm, Colin D; Drewnowski, Adam
ABSTRACT: Background: Many of the health benefits of tea have been attributed to its flavonoid content. Tea consumption in US adults varies by socioeconomic status (SES). Objectives: The present objective was to explore intakes of total flavonoids and flavonoid subclasses by participant sociodemographics and by patterns of tea consumption. Methods: The present analyses were based on 2 d of dietary recalls for 17, 506 persons aged >9 y in the 2011–2016 NHANES. The What We Eat in America nutrient composition database was merged with the USDA Expanded Flavonoid database, which included total flavonoids and flavan-3-ols (including catechins), flavanones, flavonols, anthocyanidins, flavones, and isoflavones. Flavonoid intakes were compared by sex, age, race/ethnicity, education, and income-to-poverty ratio (IPR) in univariate analyses. Flavonoid intakes of children and adults were also compared by tea consumption status. Time trends in flavonoid intakes were also examined. Results: Mean total flavonoid intake was 219 mg/d, of which flavan-3-ols provided 174 mg/d, or 79%. The highest total flavonoid intakes were found in adults aged 51–70 y (293 mg/d), non-Hispanic whites (251 mg/d) and in groups with college education (251 mg/d) and higher income (IPR >3.5: 249 mg/d) ( P  < 0.001 for all). The socioeconomic gradient was significant for anthocyanidins, flavonols, and flavones ( P  < 0.001 for all) but not for flavan-3-ols, and persisted across 3 cycles of NHANES. Adult tea consumers had higher intakes of total flavonoids (610 mg/d compared with 141 mg/d) and flavan-3-ols (542 mg/d compared with 97.8 mg/d) than did nonconsumers ( P  < 0.001). Time trend analyses showed that both tea consumption and flavonoid intakes were unchanged from 2011 to 2016. Conclusions: Flavonoid intakes in children and adults in the NHANES 2011–16 sample were associated with higher SES and were largely determined by tea consumption. Studies of diet and disease risk need to take sociodemographic gradients and eating and drinking habits into account.